Use of Doxycycline in a Patient following Minocycline-Induced Lupus - Newman, Katherine Quinn; Castles, Charles Guy (Case Reports in Rheumatology, 2023)
Minocycline, a tetracycline antibiotic, is commonly used to treat rosacea and acne vulgaris. A rare adverse reaction of minocycline use is the development of drug-induced lupus. Fortunately, most patients recover from minocycline-induced lupus (MIL) after the drug is discontinued. However, many patients, after recovering from MIL, may desire further treatment for their acne and may consider doxycycline, a close relative of minocycline. Though no cases of doxycycline-induced lupus have been reported, there is little guidance in the medical literature as to whether doxycycline poses a particular risk to patients who have recovered from MIL. We report the long-term follow-up of a patient who recovered from MIL (the diagnosis satisfying clinical and laboratory criteria) and was treated for 8 years with various forms of doxycycline without any untoward effects, suggesting that, at least in some cases, doxycycline can be used safely following MIL.